HYBRIDITY OF POLITICAL SYSTEM OF UKRAINE: ON THE WAY OF MODERNIZATION - Мислюк, Ю. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The author analyzes the model of a "hybrid" political system of modern Ukraine through such factors as lack of new political and social institutions, the dominance of the executive power, the low level of political education. A conceptual model of democratization of the political system in Ukraine by modernizing and effective leader- and elite-making, the accumulation of social capital and successful economic reform.